Diagonal Compression Test of Mortar Interlocking Masonry Walls With Various Block Shapes and Different Support Conditions - Furukawa, Aiko; Masuda, Keiya; Kiyono, Junji (Frontiers in Built Environment, 2020)
The collapse of masonry buildings has caused numerous fatalities during past earthquakes. To reduce casualties due to earthquakes, the reinforcement of masonry buildings is necessary. Since masonry buildings are still used due to the low cost of the building materials, cheap reinforcement measures are desirable. Therefore, this study investigates the use and shape of the interlocking blocks instead of the regular rectangular blocks to increase the strength of masonry buildings without using expensive reinforcing materials. First, diagonal compression tests of masonry walls made of interlocking blocks with various shapes under different support conditions were conducted. Regarding the block shapes, two types of I-shaped blocks and two types of hourglass-shaped blocks were compared. For the support conditions, glued and contact conditions were compared. Next, finite element analysis was conducted to understand the mechanism. From the experiment and the finite element analysis, a similar tendency was observed. The walls made of I-shaped blocks with a right angle have less strength than the I-shaped block walls with an obtuse angle and the two hourglass-shaped block walls. It was also found that the support condition has a slight effect on the results of the I-shaped block wall with a right angle but large effect on the results of the other three block walls where the wall under the contact condition has larger strength than the wall under the glued condition. The strain was locally concentrated where the adjacent blocks interlock with each other or the block interlocks with the jig, and failure occurred at the area where the strain was concentrated. Strength can be increased by changing the block shape with less interlocking effect such as the I-shaped block walls with an obtuse angle or hourglass-shaped block walls. However, the displacement increases due to the dislocation and rotation of blocks as the interlocking effect decreases.